ENVIRONMENTAL CONCERN UNDER INDONESIA’S PREFERENTIAL TRADE AGREEMENTS (PTAs) - I Gusti Ngurah Parikesit Widiatedja (Yustisia, 2019)
International trade has resulted positive impacts, such as alleviating poverty and increasing jobs. All countries then start concluding trade agreements multilaterally, regionally and bilaterally. The existence of preferential trade agreements is increasingly significant due to the deadlock of multilateral trade agreements. Although providing benefits, international trade has adversely affected environment. Some international treaties suggest how countries should include environmental concern in their PTAs. Unlike traditional PTAs, most of modern PTAs have incorporated environmental concern, reconciling the goal of trade liberalization and environmental protection. In Indonesia, there is a link between international trade and environmental harm. This article aims to show the existing Indonesia’s PTAs, analysing how Indonesia has put, and how it should put environmental concern in its PTAs. This article argues that only a few Indonesia’s PTAs have incorporated environmental concern in their provisions. Moreover, when they include environmental concern, there is no further elaboration on how this process should be undertaken. Compare to other existing PTAs, Indonesia should start incorporating environmental concern in its PTAs, and then allow the right of government to impose protective measure in order to preserve environment.